Antiphase Domain Boundary Formation in 2D Ba–Ti–O on Pd(111): An Alternative to Phase Separation. Issue 1 (13th January 2022) - Wührl, Friederike Elisa; Krahn, Oliver; Schenk, Sebastian; Förster, Stefan; Widdra, Wolf
Abstract : Surface science studies of two‐dimensional Ba–Ti–O films on Pd(111) identify three different small unit cell structures (see article number 2100389 by Stefan Förster and co‐workers). In scanning tunneling microscopy these structures exhibit an atomic base of four atoms of one species, decorating the vertices of two triangles. As depicted on the cover, this base rearranges upon atomic density variations. In a fully stretched‐out fashion (left side), corresponding to the lowest density state, a square lattice is formed. In the high‐density limit (right side) a rectangular structure forms, in which rhombuses fill the gaps. The medium density motif incorporates squares and rhombuses.